IPTEKS AKUNTANSI PERTANGGUNGJAWABAN PUSAT PENDAPATAN PT. BANK MANDIRI - Kumaat, George Evander; Maradesa, Djeini (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. Bank Mandiri (Persero) Tbk is a state-owned company that collects funds from the public in the form of deposits and redistributes them to the community in the form of loans to improve people's lives. The majority of PT Mandiri Bank's revenues are obtained from the credit system offered. The income earned is regulated by the center of accountability in this case the revenue center. From this, the research was conducted in order to find out the application of PT Mandiri Bank's revenue centers. Assessment is carried out by applying the revenue center marketing method.Keywords : accountability, revenue center, marketing method